Unveiling the origin of Atahuallpa: myths and nationalisms in tension - Vizcaíno Haro, Jaime (Revista Ecos de la Academia, 2023)
The birthplace of Atahuallpa has been the source of various theories of narrators and chroniclers who have used history and memory in order to reveal its origin, as well as understand the reasons for one of the largest civilizations in America to come to an end. This article is the product of a bibliographical investigation of more than twenty historical and contemporary sources that provide clues that prove that Caranqui, in the kingdom of Quito, was the homeland of the last Inca of Tahuantinsuyo. In addition, the implications of the conflict between brothers, hecatombs, animosities in expansionist campaigns, betrayals due to the hunger for gold and resistance in the conquest that gave rise to the future territorial claim between Ecuador and Peru are explored.